The Effect of Transfer Pricing and Leverage on Tax Avoidance with Independent Commissioners as Moderation: Study of Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2019-2024 Period (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and analyze the influence of Transfer Pricing and Leverage on Tax Avoidance with independent commissioners as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 – 2024. The study method applied in this study is an explanatory study method. In this study, study objects are divided into two types, namely material and formal objects. This study applies a quantitative approach with the characteristics of a replication study. The sampling technique used in this study is purposive sampling with a total of 486 annual financial statements. Using moderation regression analysis, this study shows that Transfer Pricing has a negative and significant effect on Tax Avoidance, while Leverage has a positive and significant effect on Tax Avoidance. Independent commissioners are not able to moderate the effect of transfer pricing on tax avoidance and independent commissioners are not able to moderate the effect of leverage on tax avoidance.